Workshop on Financial and Tax Reports for MSMEs in Tenjoayu - Kurniasih Dwi Astuti; Dabella Yunia; Windu Mulyasari; Nana Nofianti; Galih Fajar Muttaqin (EQUATOR SINAR AKADEMIA, 2021)
This community service tries to identify, analyze and solve financial report problems for Micro, Small and Medium Enterprises in Tenjoayu Village, Serang Banten. As a village that is in its infancy, Sindangsari Village requires the intervention of academics to improve the quality of human resources in accordance with the existing potential. The basic problem for Micro, Small and Medium Enterprises in Tenjoayu Village is the low knowledge of financial reports and taxation of Micro, Small and Medium Enterprises in Tenjoayu Village. This community service is carried out using persuasive methods for Micro, Small and Medium Enterprises in Tenjoayu Village, lectures, and field practice. This activity aims to improve the quality of human resources in Micro.